REFORMASI BIROKRASI DALAM MEWUJUDKAN PEMERINTAH YANG BEBAS DARI KORUPSI, KOLUSI DAN NEPOTISME - La Sina (Faculty of Law, Universitas Diponegoro, 2012)
In the current of reform era, is still discovered by the government bureaucracy, as an organizer of the state, it's not doing a good job, even, they do not serve the people but they to be served. Today the government has sought spawned a lot of regulations as a basis for providing services to the community. The reform of the bureaucracy, which the public expects it, is convenience for the public to obtain an optimal service. Government bureaucracy in realizing good governance, must be based on the authority in accordance with laws and regulations, principles of state organization, and also the execution of bureaucracy reform is carried out through the alignment of government institutional arrangement, bureaucracy and the iterative improvement of the quality of public service. In carrying out the bureaucracy that is free from corruption, the bureaucrats as the organizer of the state must be away from acts that are damage the joints of the affected communities, nation and state. Keywords : the reform of birocration, government, corruption, coluusion and nepotism